I really don't get what I'm supposed to do with this problem. If someone could show me the steps, that would be great. radical (x + 1) = x - 1 (that's supposed to be a radical sign over the x+1)
Follow Math Help Forum on Facebook and Google+
Originally Posted by SwissArmelle I really don't get what I'm supposed to do with this problem. If someone could show me the steps, that would be great. radical (x + 1) = x - 1 (that's supposed to be a radical sign over the x+1) square both sides and solve for x. then check your solutions in the original equation to make sure none are extraneous
$\displaystyle \begin{aligned} \sqrt {x + 1} &= x - 1\\ x + 1 &= x^2 - 2x + 1\\ x^2 - 3x &= 0\\ x(x - 3) &= 0\\ x_2 &= 3 \end{aligned}$ Greetings (see why $\displaystyle x=0$ is refused)
View Tag Cloud